2004
DOI: 10.1101/gad.1176004
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of protein phosphatase 5 in DNA-damage-induced ATM activation

Abstract: The checkpoint kinase ATM is centrally involved in the cellular response to DNA double-strand breaks. However, the mechanism of ATM activation during genotoxicstress is only partially understood. Here we report a direct regulatory linkage between the protein serine-threonine phosphatase 5 (PP5) and ATM. PP5 interacts with ATM in a DNA-damage-inducible manner. Reduced expression of PP5 attenuated DNA-damage-induced activation of ATM. Expression of a catalytically inactive PP5 mutant inhibited the phosphorylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
153
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(156 citation statements)
references
References 29 publications
2
153
0
1
Order By: Relevance
“…Disruption of PP5 activity by siRNA resulted in defects in ATM activation and radioresistant DNA synthesis. In addition, the phosphatase activity of PP5 was shown to be required for ATM autophosphorylation and activation (Ali et al, 2004). These findings suggest that PP5 might control ATM kinase activity by dephosphorylating ATM, the MRN complex, or other factors involved in ATM activation.…”
Section: Likely Candidates For Inactivators and Activators Of Atmmentioning
confidence: 88%
See 2 more Smart Citations
“…Disruption of PP5 activity by siRNA resulted in defects in ATM activation and radioresistant DNA synthesis. In addition, the phosphatase activity of PP5 was shown to be required for ATM autophosphorylation and activation (Ali et al, 2004). These findings suggest that PP5 might control ATM kinase activity by dephosphorylating ATM, the MRN complex, or other factors involved in ATM activation.…”
Section: Likely Candidates For Inactivators and Activators Of Atmmentioning
confidence: 88%
“…Recent articles show that two phosphatases, protein phosphatase 2A (PP2A) and protein phosphatase 5 (PP5), both affect ATM activity in vivo (Ali et al, 2004;Goodarzi et al, 2004). PP2A is a member of the protein serine/threonine phosphatase family and is composed of a catalytic (C) subunit, a scaffolding A subunit and a regulatory B subunit.…”
Section: Likely Candidates For Inactivators and Activators Of Atmmentioning
confidence: 99%
See 1 more Smart Citation
“…What is not clear yet is whether ATM pS367 and pS1893 coincide with pS1981 at the break site or whether they are associated with movement of ATM from the site to the flanking regions. Not surprisingly, protein phosphatases have also been shown to play a role in ATM activation (Ali et al, 2004;Goodarzi et al, 2004). DNA-damaged-induced acetylation of ATM has been reported by Sun et al (2005) and this was shown to run in parallel with pS1981 after radiation exposure.…”
Section: Perspectivementioning
confidence: 95%
“…Earlier studies have shown a role for PP5 in the activation of cell cycle checkpoints in response to DSBs. Thus, MEFs from PP5 deficient mice exhibit a reduction in ATM activation subsequent to DSBs and an alteration in the G2/M checkpoint (Ali et al, 2004). In this context a role for PP5 in the activation of PARP-1 is aligned with a role for PP5 in the activation of ATM.…”
Section: Discussionmentioning
confidence: 94%